RETORIKA DAN KESIAPAN MENTAL PENYULUH AGAMA HINDU - I Kadek Abdhi Yasa; Duwi Oktaviana (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2020)
Religious Instructor is a profession related to the delivery of religious teachings to the people. Likewise with the existence of Hindu religious instructors who are now very much needed to become a stronghold of Hindu society from various problems in the mental and spiritual realm. Along with the rapid development of communication technology causing patterns of community life to be so complex, the negative thing that arises is the social disparities in society. This gap arises because of misuse of existing communication technology. This is where the role of a religious instructor to provide mental knowledge as spiritual for the people especially Hindus. A trainer is expected to be able to have good rhetorical and mental abilities as a basic capital in conducting rhetoric counseling is a technical that is related to the application of language as an art, both oral and written, which is based on well-structured understanding, and arises from natural talent and from an knowledge well organized to attract the attention of the listener or reader. Mental readiness is related to mind control, self-readiness, self-confidence, relief of fear, and good practice. these two conceptions need to be studied and mastered by an instructor to become a quality instructor.Keywords : Rhetoric, Mental Readiness, and Religious Counselors